Validity of the Six-Minute Walk Test in Cancer Patients - Schmidt, K.; Vogt, L.; Thiel, C.; Jäger, E.; Banzer, W. (International Journal of Sports Medicine, 2013)
The present study evaluated the validity of the six-minute walk test (6MWT) in cancer patients. 50 subjects (36 f, 14 m; 57.4±10.2 years; during (56%) or off (44%) cancer treatment) performed a 6MWT and a spiroergometry on a cycle ergometer (0+25 W, 3 min) to evaluate maximum exercise capacity (VO2peak). A subsample (n=30) completed a retest of the 6MWT within 2–7 days. Patients covered a distance of 594±81 m during 6MWT at an average intensity of 86.3±9.6% of HRmax and achieved a VO2peak of 21.2±4.86 ml · kg − 1 · min − 1 during cycle ergometry. The distance walked correlated significantly (p<0.001) with VO2peak (r=0.67) and perceived physical function (EORTC QLQ-C30 physical function subscale) (r=0.55). Concerning reliability the intraclass correlation coefficient was r=0.93 (95%CI: +0.86;+0.97; p<0.001) and the coefficient of variation 3%. During retest participants walked 3.1% (95%CI: +1.1; +5.2) farther and achieved a higher RPE (+1.0; 95%CI: +0.3;+1.8). Limits of agreement were between  − 43.1 and 76.4 m. In cancer patients the 6MWT seems to be as valid and reliable as in healthy elderly, cardiac and pulmonary patients. Thus, it can be recommended for use in cancer patients.
Keywords: reliability; validity; 6MWT; cancer; evaluation of physical function